A Multicultural Communication Modelof Scienceand Technology - Rueda Romero, Xenia A. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2015)
This article discusses some problems that exist around the communication of science and technology, which are transmitted on a linear model that matters only to publicize the progress and benefits of science and technology. The main thesis will be to sketch a model of communication of science and technology for a multicultural society, in which it proposes that it is not only important to convey the scientific and technological knowledge, but also communicate and respect traditio-nal knowledge, which is immersed in a multicultural society like ours.